The Use of a PEG/Ascorbate Booster Following Standard Bowel Preparation Improves Visualization for Capsule Endoscopy in a Randomized, Controlled Study - Miguel José Mascarenhas-Saraiva; Eduardo Oliveira; Miguel Nuno Mascarenhas-Saraiva (Turkish Journal of Gastroenterology, 2021)
Background/Aims: The increasing use of capsule endoscopy (CE) to examine the gastrointestinal tract highlights the need to establish intestinal preparations that ensure optimal visualization while maximizing patient adherence. Thus, we assessed whether bowel preparation involving dietary restriction and a booster regimen produces adequate CE visualization in a real-world clinical setting. Methods: We conducted a randomized, double-blind, prospective study of CE procedures at 2 tertiary-care centers. Patients were allocated to 3 groups: group 1 followed a clear liquid diet and fasting-based bowel preparation for the exploration (n = 55); group 2 followed the same procedure as group 1 and then ingested 1 L of a polyethylene glycol (PEG)/ascorbic acid booster solution when the capsule reached the small intestine (n = 55); and group 3 followed the same procedure but ingesting only 0.5 L of the booster solution (n = 56). The quality of visualization and the average gastric, orocecal and small-bowel transit times were evaluated. Results: A total of 166 patients participated in the study. Significantly higher quality of visualization (Park score) was obtained in group 3 (2.28 ± 0.59) than in group 1 (1.84 ± 0.54, P < .001), while there were no significant differences in the average gastric (range: 36.58- 48.32 min, P = .277), orocecal (range: 322.58-289.45 min, P = .072), and small-bowel transit time (range: 280.71-249.95 min, P = .286) between the 3 groups. Conclusions: Following a clear liquid diet and fasting-based bowel preparation for CE exploration, administering a booster solution of PEG/ascorbic acid after the capsule had reached the small intestine improves mucosal visualization and cleansing without affecting capsule transit times. Cite this article as: Mascarenhas Saraiva MJ, Oliveira E, Mascarenhas Saraiva MN. The use of a PEG/ascorbate booster following standard bowel preparation improves visualization for capsule endoscopy in a randomized, controlled study. Turk J Gastroenterol. 2021; 32(5): 437-442.